Հայոց Ազգագրութեան թանգարանի աղօթագորգերի հաւաքածուն - Մխիթարեան, Անի (տպ. Atlas)
Due to their artistic decoration and particularly their design, prayer rugs are classified as alter rugs. They have a ritual significance. Today they are common in the Muslim world and are used during namaz prayers (Aghotagorg in Armenian). Aghotagorgs were widespread in Armenian carpet weaving culture and were made in large quantities. In fact, in addition to being used in churches, these were also used for commercial purposes. The Museum of Armenian Ethnography preserves about thirty Aghotagorgs (without columns) enriched with Armenian ornaments with symbolic significance. They differ in their types, variety of architectural arches and symbolic images. The paper divides the Aghotagorgs into two major groups: a) those having the interior design of an Armenian Church and b) those which have pillar designs. The paper focuses on the first group of Aghotagorgs and categorizes them according to their design.
Keywords: Թանգարաններ; Գորգագործութիւն; Ազգագրութիւն